1997
DOI: 10.1002/(sici)1096-9861(19971110)388:1<106::aid-cne7>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated astrocyte reactivity after nigrostriatal deafferentation in the aged rat

Abstract: Although clinical experience suggests that brain injury in the aged is associated with a poor prognosis, little research has examined this phenomenon at a cellular or molecular level. Unilateral 6-hydroxydopamine lesions of the nigrostriatal system were produced in 6-, 15- or 24-month-old rats. In the deafferented neostriatum, the time-dependent induction of glial fibrillary acidic protein (GFAP) was larger and persisted longer in the aged rats. The response of middle-aged rats was intermediate. In contrast, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Generally there is an increased astrocytic reaction following injury to the aging CNS. For example, Gordon et al (1997) found that nigrostriatal deafferentation causes a time-dependent induction of GFAP that is larger and more persistent in aged rats than in young animals. Interestingly, the authors noted an intensification of GFAP staining in the contralateral hemisphere of aged (but not young) rats, a phenomenon that was confirmed by our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Generally there is an increased astrocytic reaction following injury to the aging CNS. For example, Gordon et al (1997) found that nigrostriatal deafferentation causes a time-dependent induction of GFAP that is larger and more persistent in aged rats than in young animals. Interestingly, the authors noted an intensification of GFAP staining in the contralateral hemisphere of aged (but not young) rats, a phenomenon that was confirmed by our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was performed as previously described. 22 Briefly, paraffin-embedded slices (4 μm) were quenched to inactivate endogenous peroxidase for 30 minutes using 0.5% H 2 O 2 ; then, the nonspecific binding sites were blocked using 5% BSA (bovine serum albumin) at room temperature for 1 hour. The sections were incubated overnight at 4°C with Cleaved-caspase-3 (CASP3) antibody Immunofluorescence microscopy was performed on brain and cell slices as previously described.…”
Section: Immunohistochemistry and Immunofluorescencementioning
confidence: 99%
“…Immunohistochemical analysis of ␣ 7 nAChRs was performed using 25-m free-floating sections spaced 300 m apart through the hippocampus. Details of this procedure were originally described elsewhere (Gordon et al 1997). All steps were performed on a rotating platform at ‫ف‬ 40 rpm, room temperature, unless otherwise stated.…”
Section: Histologymentioning
confidence: 99%